If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 31 = 4 + -3x Solving 31 = 4 + -3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3x' to each side of the equation. 31 + 3x = 4 + -3x + 3x Combine like terms: -3x + 3x = 0 31 + 3x = 4 + 0 31 + 3x = 4 Add '-31' to each side of the equation. 31 + -31 + 3x = 4 + -31 Combine like terms: 31 + -31 = 0 0 + 3x = 4 + -31 3x = 4 + -31 Combine like terms: 4 + -31 = -27 3x = -27 Divide each side by '3'. x = -9 Simplifying x = -9
| 4w=49-3w | | -22.5=6-3.3 | | (4x^2)(x+3)=0 | | 5-4.5*d=32 | | 36-Y=173 | | 11.1+.5=1.4 | | 12-3(3m-2)=8-2(4m+2) | | 177=45-x | | y=(x^4)-(98x^2) | | 5u+10=110 | | xy+3z+(-3xy)=3xy+3z+(-3xy) | | 3xy+3z*-3xy=3xy+3z*-3xy | | 9x+28y=37 | | 2x+21+3x-2=52-4x+30 | | (3xy)+3z(-3xy)= | | 180=x*2.54 | | 1=3x-1/5x+2 | | 12234+1= | | -9-7f=12 | | -5+-1=3 | | f(n)=f(n-1)+8 | | Y=-6(40)+110 | | 20x+45y=15965 | | Y=-6x+110 | | (2.7)x(2.7)(4)(2.7)2=(2.7)2 | | -2y=3-x | | -63+6y+2=3(4y-4)-7 | | 3(x-6)=2x-6 | | 4.5x=-60.75 | | x=10-10 | | 0.4*b+1=-11 | | 0.04x+0.07y=260 |